Establishing Validity And Reliability Of Newly Developed Professionalism Assessment Tool - Noreen, Khola; Zuberi, Rukhsana; Ali, Kashif; Meraj, Lubna (Journal of Rawalpindi Medical College, 2025)
Objective: This study aims to establish construct validity and reliability of a newly developed tool for assessment of professionalism in undergraduate medical students. Method: The study was carried out after establishing feasibility and obtaining ethical approval from Aga Khan University and Rawalpindi Medical University. Data was collected from 3rd-year and 4th-year undergraduate medical students at the end of 2-week rotations. The tool was initially administered to year 4 MBBS students (pilot test); the data obtained was analysed by principal component factor analysis and reliability analysis to estimate the construct validity and reliability. A total of 391 Year 3 medical students were assessed using the 16-item PAT. The principal component analysis (PCA) and reliability analysis were conducted, thus further establishing the validity and reliability of the tool. Result: Four factors were obtained on exploratory PCA. Nine items loaded on Factor 1 and merged the items on the proposed P-SS2 and P-SS3 subscales of “Ethics and personal characteristics” into one (SS1). SS2 was validated as all three items loaded on this subscale were related to “Effective communication and doctor-patient relationship.” SS3 and SS4 separated the four items included in the P-SS4 of ‘Supports Community Needs and Others’ into SS3 of “Respects and Supports Others” and into SS4 with items related to “collegiality: Responsive to Community Needs and Other Health Professionals.” The 16-item PAT had an overall reliability (Cronbach’s alpha) of 0.856. The Reliability of the new Subscales obtained after PCA for SS1 was 0.767, for SS2 was 0.726, for SS3 was 0.568 and for SS4 was 0.380. Conclusion: The final tool developed for assessment of professionalism had 16 items on a 7-point Likert-like scale, across 4 Subscales. It can be used as a reliable and valid tool for assessment and feedback of professionalism for undergraduate medical students.